IJCM_329A: Prevalence of Impostor Phenomenon and its association with Depression, Anxiety and Stress in undergraduate medical students - Alok Yash; Kenguva Nikhil Kumar; Sufyan Mohd; Udupa Suma T (Wolters Kluwer Medknow Publications, 2024)
Background: Clance and Imes coined the term "impostor phenomenon," or IP, which causes a person to choose to elevate the achievements of others and belittle their own successes. This results in constant self-underappreciation and anxiety about a task. The field of medical science is a highly pressure-intensive and competitive field. In the medical field, where patients' lives are involved daily, a condition like this which is going undiagnosed, will affect the duties provided by the medical practitioner in the long run. They will doubt every decision they make, which can seriously harm the patient. All these reasons show the necessity of discovering new and more advanced techniques to identify the disorder. As a result, this condition develops into more severe forms. It results in more serious psychiatric conditions that can be prevented if IP is identified correctly. Objective: To identify the prevalence of Imposter Phenomenon and to find its associations with depression, anxiety, and stress in medical students Methodology: It was a cross sectional study done among undergraduate students of a private medical college in Manipal. About 377 undergraduates participated in the study. Data was collected using the Clance IP scale and DASS-21 questionnaire after taking relevant permissions. The data was collected in an excel sheet from the responses derived from the Microsoft form. Data was analyzed using the open-source statistical software Jamovi 2.0. Results: It was observed that more than half of the students were female. More than two fifths of the students reported having frequent IP experiences, and about 15% of them reported intense IP experiences. Positive correlation was observed between IP and Stress, Anxiety and Depression. Conclusion: Impostor Phenomenon should be diagnosed and identified early in medical undergraduates to reduce mental health issues in the long run so they may be able to provide quality medical care.